2017
DOI: 10.1162/comj_a_00397
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the Klangdom Live: Cartographies for Piano with Two Performers and Electronics

Abstract: This is the published version of the paper.This version of the publication may differ from the final published version. Abstract: The use of high-density loudspeaker arrays (HDLAs) has recently experienced rapid growth in a wide variety of technical and aesthetic approaches. Still less explored, however, are applications to interactive music with live acoustic instruments. How can immersive spatialization accompany an instrument already with its own rich spatial diffusion pattern, like the grand piano, in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 7 publications
0
12
0
Order By: Relevance
“…The clustering algorithm used in CiteSpace is the interclass distance algorithm in hierarchical clustering algorithms. One of the most common is the interclass average distance algorithm with the formula shown in (13). Where p, q are two clustering clusters, the determination of the distance between them relies on the average distance between cells i, j:…”
Section: Cluster Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The clustering algorithm used in CiteSpace is the interclass distance algorithm in hierarchical clustering algorithms. One of the most common is the interclass average distance algorithm with the formula shown in (13). Where p, q are two clustering clusters, the determination of the distance between them relies on the average distance between cells i, j:…”
Section: Cluster Analysismentioning
confidence: 99%
“…Piano in today's music performance has played an increasingly important role [13] for the majority of the audience to bring a different visual, sensory, and auditory experience, not only helps the audience listeners to improve the overall quality but also for the audience aesthetic ability to improve the role of different degrees of promotion [14][15]. Throughout the evolution and development of the piano playing method, it can be said that it has gone through tremendous changes, from the tiny finger movements playing to the application of arms as well as body weight has been greatly improved [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Literature [9] used a laboratory virtual instrument work platform to design a piano key recognition device, which can accurately judge and recognize the piano key corresponding to the tone through the piano tone. Literature [10] reveals that the application of high-density loudspeaker arrays to enhance the music immersion experience, as well as the three-dimensional projection of musical instrument layouts in concert halls, adds to the interactive experience of the music performance and the audience. Literature [11] examined musical compositions created by the fusion of piano performance and computer systems, where the iterative changes in notes were presented in graphical form, and found that the style of the compositions created tended to be simplistic.…”
Section: Introductionmentioning
confidence: 99%
“…The flavor of piano music is embedded in the style. That is, piano music has been produced through several different historical periods of piano music, and the piano works of each period have their unique style characteristics and other performance techniques [1][2]. These differences are due to the different creative ideas of the composers, as well as the various backgrounds of the times in which they lived, and the many differences in their life experiences, all of which are presented in different piano music works [3][4].…”
Section: Introductionmentioning
confidence: 99%